2018
DOI: 10.1093/hmg/ddy237
|View full text |Cite
|
Sign up to set email alerts
|

Consortium-based genome-wide meta-analysis for childhood dental caries traits

Abstract: Prior studies suggest dental caries traits in children and adolescents are partially heritable, but there has been no large-scale consortium genome-wide association study (GWAS) to date. We therefore performed GWAS for caries in participants aged 2.5–18.0 years from nine contributing centres. Phenotype definitions were created for the presence or absence of treated or untreated caries, stratified by primary and permanent dentition. All studies tested for association between caries and genotype dosage and the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 70 publications
0
38
0
2
Order By: Relevance
“…The most recent example is a meta-analysis of studies that include dental caries assessments ranging from self-reported questionnaire to standard clinical examinations for more than 13,000 children 2 to 18 years of age. The reduction of the phenotype to having at least one lesion versus having no lesions from scores obtained in primary and permanent dentitions led, not surprisingly, to meaningless results [19]. Here, we are reporting how differences observed in the enamel surface measured through scanning electron microscopy without any known bias on how these measurements were generated associate with genetic variants in genes previously associated with dental caries from hypothesis driven work.…”
Section: Discussionmentioning
confidence: 96%
“…The most recent example is a meta-analysis of studies that include dental caries assessments ranging from self-reported questionnaire to standard clinical examinations for more than 13,000 children 2 to 18 years of age. The reduction of the phenotype to having at least one lesion versus having no lesions from scores obtained in primary and permanent dentitions led, not surprisingly, to meaningless results [19]. Here, we are reporting how differences observed in the enamel surface measured through scanning electron microscopy without any known bias on how these measurements were generated associate with genetic variants in genes previously associated with dental caries from hypothesis driven work.…”
Section: Discussionmentioning
confidence: 96%
“…Genome-wide association studies (GWAS) for dental caries have investigated measures, including overall caries experience 6,7 , specific presentations of disease and the presence or absence of disease in paediatric populations 8,9 . To date, few reliable genetic-association signals have been found, and this is likely to reflect different measurement approaches used, complex genetic architecture 10 of dental caries or limited statistical power to detect associations.…”
Section: Introductionmentioning
confidence: 99%
“…Repositories such as the Human Oral Microbiome database and the Human Microbiome Consortium have emerged as data aggregate to provide standardized and easily accessible sources of oral microbiome genomic and taxonomic data to researchers and clinicians alike . Genome‐wide association studies have also been performed on traditionally at‐risk populations such as US Hispanics and children to further identify characteristics that can be used to stratify these patients . However, the relationship between genetics and caries risk is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Genome-wide association studies have also been performed on traditionally at-risk populations such as US Hispanics and children to further identify characteristics that can be used to stratify these patients. 65,66 However, the relationship between genetics and caries risk is still unclear. Currently, these studies have only found modest associations between gene variants and caries risk.…”
Section: Where To Gather Datamentioning
confidence: 99%